Transfer of spin reorientation in a NdCo5/Fe bilayer. (19th July 2016) - Teixeira, B M S; Timopheev, A A; Schmidt, R; Soares, M R; Seifert, M; Neu, V; Sobolev, N A
Abstract: A NdCo5 (37 nm)/Fe (22 nm) hard/soft bilayer was grown by pulsed laser deposition on a MgO (1 1 0) substrate, and investigated by vibrating sample magnetometry and ferromagnetic resonance (FMR). Due to the direct exchange coupling at the NdCo5 /Fe interface, the spin reorientation transition (SRT) typical of NdCo5 is observed also in the bilayer by means of global magnetometry. Concerning the magnetization dynamics, the interlayer magnetic coupling is weak, thus allowing the identification of the FMR signals in the sample as those originating mainly from the individual responses of the Fe and NdCo5 layers. In the NdCo5 layer, the effective coupling field is negligible compared to the internal anisotropy, and the magnetization precession is similar to the one found in a NdCo5 single layer. In the magnetically soft Fe layer, however, the precession of the moments occurs in the exchange field stemming from the dynamically fixed NdCo5 layer, giving rise to a partial transfer of magnetic anisotropy from the latter and enabling us to follow the SRT of NdCo5 by measuring the Fe FMR peak field position. Controlling the anisotropy direction in the soft layer by making use of the SRT in the hard layer can find applications in future spintronic devices.